2020
DOI: 10.1177/1932296820947094
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Implementation of a Diabetes Telemedicine Clinic During the Coronavirus Disease 2019 Outbreak: Our Protocol, Experience, and Satisfaction Reports in Saudi Arabia

Abstract: Background: The importance of telemedicine in diabetes care became more evident during the coronavirus disease 2019 (COVID-19) pandemic as many people with diabetes, especially those in areas without well-established telemedicine, lost access to their health care providers (HCPs) during this pandemic. Subjects and Methods: We describe a simplified protocol of a Diabetes Telemedicine Clinic that utilizes technological tools readily available to most people with diabetes and clinics around the world. We report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 28 publications
3
61
0
1
Order By: Relevance
“…The participants thought that telemedicine is not suitable for all medical cases, and most of them thought that chronic disease follow-up is the most suitable to be cared for by telemedicine. A systematic review done in 2019 supported our result and showed that to manage COVID-19, there are many easy-to- set-up potentials in live video consulting [ 24 ]. Studies have found that live video conferencing can lead to the avoiding of direct physical contact, thereby diminishing the risk of exposure to respiratory secretions, and preventing the potential transmission of infection to physicians and other healthcare providers [ 25 ].…”
Section: Discussionsupporting
confidence: 59%
“…The participants thought that telemedicine is not suitable for all medical cases, and most of them thought that chronic disease follow-up is the most suitable to be cared for by telemedicine. A systematic review done in 2019 supported our result and showed that to manage COVID-19, there are many easy-to- set-up potentials in live video consulting [ 24 ]. Studies have found that live video conferencing can lead to the avoiding of direct physical contact, thereby diminishing the risk of exposure to respiratory secretions, and preventing the potential transmission of infection to physicians and other healthcare providers [ 25 ].…”
Section: Discussionsupporting
confidence: 59%
“…Although patient resistance to telemedicine was an important consideration among our respondents, a majority felt that patient satisfaction to telemedicine is likely to be high. High patient satisfaction with telemedicine has been reported by many studies in the past, including a recent study from Saudi Arabia, conducted during the COVID-19 pandemic [1].…”
Section: Discussionmentioning
confidence: 93%
“…The COVID-19 pandemic has led to an increased use of telemedicine all over the world, including Saudi Arabia [1,2]. It is possible that telemedicine will form an integral part of the "new normal."…”
Section: Introductionmentioning
confidence: 99%
“…The lack of broadband internet access in some parts of the world, need for some technical literacy, and risk of loss of privacy are other limitations to the wide adoption of telemedicine. However, we have previously shown that the adoption of a simple diabetes telemedicine protocol, that does not require technological tools or skills other than those widely available to most PWD and HCPs, is a feasible option that is associated with both high patients' and HCPs' satisfaction and low worries about loss of privacy 32 . Whether the same applies to PWD who also have mental illnesses remains unknown and warrants future studies.…”
Section: Discussionmentioning
confidence: 99%